Evaluation of Luteinizing Hormone, Follicle Stimulating Hormone and LH/FSH Ratio in Polycystic Ovary Syndrome of Reproductive Women - Akhter, Salma; Chowdhury, Nafisa Marzan; Chowdhury, Palash; Barua, Upasana; Parvin, Ayesha; Barua, Lopa; Yasmin, Monira (Eastern Medical College Journal, 2025)
Background: Polycystic Ovary Syndrome (PCOS) is an endocrine disorder that affects women of reproductive age. Disturbances in luteinizing hormone (LH), follicle stimulating hormone (FSH), and the LH/FSH ratio are pivotal pathophysiological features of PCOS. The objective of this study is to assess the concentrations of various hormones (LH, FSH and LH/FSH ratio) in patients with PCOS. Materials and methods: This cross-sectional comparative study was conducted in Chittagong Medical College & Hospital. The sample size was 100 comprising 80 individuals in the PCOS group (Group A) and 20 healthy reproductive women in the control group (Group B). The sampling technique was non-probability consecutive sampling. Results: Serum LH levels were increased in 22.5% of PCOS cases. The mean serum LH and LH/FSH ratios were significantly different between PCOS group and healthy group (7.54 ± 0.51 vs. 5.77 ± 0.63 mIU/ml) and (2.05 ± 0.18 vs. 1.25 ± 0.18 mIU/ml) respectively. Mean serum FSH levels did not show significant difference between the PCOS and healthy groups. Distribution of menstrual history, hirsutism and family history of PCOS between group A and group B has statistical difference. Conclusion: Serum LH levels were significantly associated with polycystic ovarian syndrome (PCOS) in reproductive women. Therefore, assessing LH levels in PCOS may provide foundational information for early diagnosis and management of infertility associated with the syndrome. Eastern Med Coll J. July 2025; 10 (1): 13-17